2004
DOI: 10.2337/diabetes.53.11.2824
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Glucagon-Like Peptide-1 and Transforming Growth Factor-β Signaling in Insulin-Positive Differentiation of AR42J Cells

Abstract: The differentiation of pancreatic exocrine AR42J cells into insulin-expressing endocrine cells has served as an important model for both endogenous in vivo ␤-cell differentiation as well as potential application to ␤-cell engineering of progenitor cells. Exogenous activin, possibly working through intracellular smad 2 and/or smad 3, as well as exogenous exendin-4 (a long-acting glucagon-like peptide-1 agonist) have both been shown to induce insulin-positive/endocrine differentiation in AR42J cells. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…All of the NFAT sites studied in the rat I insulin promoter are responsive to the combination of glucose and GLP-1, although NFAT2 was relatively insensitive to GLP-1 alone (Lawrence et al, 2002) Schema outlining the signaling mechanisms reported to be involved in GLP-1R-induced differentiation/neogenesis of pancreatic precursor cells, proliferation and in the prevention of apoptosis. Dashed lines indicate mechanisms that are either not fully delineated or in the case of the cAMP activation of the MEK pathway are complex and are shown completely in Fig 2. The mechanism shown for involvement of BMP and TGFβ signaling pathways in differentiation is after Gittes and co-workers Yew et al, 2004). PKB is shown as inhibiting FoxO1 (by phosphorylation).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All of the NFAT sites studied in the rat I insulin promoter are responsive to the combination of glucose and GLP-1, although NFAT2 was relatively insensitive to GLP-1 alone (Lawrence et al, 2002) Schema outlining the signaling mechanisms reported to be involved in GLP-1R-induced differentiation/neogenesis of pancreatic precursor cells, proliferation and in the prevention of apoptosis. Dashed lines indicate mechanisms that are either not fully delineated or in the case of the cAMP activation of the MEK pathway are complex and are shown completely in Fig 2. The mechanism shown for involvement of BMP and TGFβ signaling pathways in differentiation is after Gittes and co-workers Yew et al, 2004). PKB is shown as inhibiting FoxO1 (by phosphorylation).…”
Section: Discussionmentioning
confidence: 96%
“…The Gittes laboratory (Yew et al, 2004) have expanded on these observations and performed a dose-response curve for Ex-4 (1 pM -100 nM) conversion by quantifying insulin II, pdx-1, and IAPP mRNA levels (Yew and colleagues supplemented their media with 20% FBS). They found that 5 pM of Ex-4 was the most effective dose over a 3 day treatment period.…”
Section: In Vitro Determination Of the Mechanism Of β Cell Differentimentioning
confidence: 99%
“…1a, b), newly generated beta cells of Insulin-Timer embryos [24] and in acinar cells of the human adult pancreas [23], we hypothesised that GLP-1 may function in non-beta cells, including acinar and duct cells, and we activated the GLP-1 signalling pathway by the administration of exendin-4, a long-acting GLP1R agonist, and by overexpressing GLP1R in exocrine cells. Whereas in vitro studies have shown that GLP-1 and exendin-4 induce beta cell differentiation in the pancreatic tumour cell line AR42J [7,9], our present study revealed that exendin-4 itself fails to initiate beta cell neogenesis in SOX9-lineage exocrine cells in vivo, even after the overexpression of GLP1R (Fig. 3f-i).…”
Section: Discussionmentioning
confidence: 54%
“…Among the many humoral factors that regulate pancreas development, glucagon-like peptide-1 (GLP-1) and its analogue, exendin-4, have been reported to affect beta cell differentiation under in vitro and ex vivo conditions [7][8][9]. In addition, previous in vivo studies showed that the co-activation of GLP-1 and gastrin signalling increased the number of beta cells in mouse models of diabetes [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Although our results indicate that bon and snail can be regulated by Smad3, our data do not rule out co-regulation by Smad2, and regulation of these genes most likely occurs via cooperation between these two Smads. Nevertheless, there are structural/functional differences between both Smads, several of which appear to distinguish their actions in vitro (Yew et al, 2004;Uemura et al, 2005;Ju et al, 2006) and in vivo (Dunn et al, 2005;Wang et al, 2006). In addition, the ratio of Smad2 versus Smad3 influences their respective roles as effectors (Dunn et al, 2004;Kim et al, 2005).…”
Section: Ttrap Distinctly Modulates Smad3 and Not Smad2 Activitymentioning
confidence: 99%